Análisis de la incidencia del endeudamiento externo sobre el Crecimiento Económico en Ecuador, periodo 2000 – 2015 - Burneo Rosillo, Danilo Emilio (2017)
External debt has proved to be one of the most feasible ways to solve the economic problems of an economy, reactivating it and positively influencing its level of growth. However, the impact on debtor countries as creditors, in the face of a situation of over-indebtedness, can generate destabilization and / or crisis on both sides that influence their level of investment, consumption, and thus their economic growth. In this context, the present study investigated the effect of external indebtedness, through a descriptive - econometric analysis, with the purpose of establishing its incidence on economic growth in Ecuador, period 2000 - 2015. For this, secondary information was taken from the base of data from the Central Bank of Ecuador (ECB), the World Bank (WB) and the International Monetary Fund (IMF). As one of the most relevant results, it was found that in Ecuador during the last 16 years it has played an important role in economic growth, and there is an inverse relationship between these two variables in the medium and long time, that is to say, the injection of capital of external financing has not been used adequately in the diversification of the productive matrix, much less strengthen the productive apparatus of the country. Likewise, the present study estimated a Laffer curve for external i and determined that these study variables are related positively and negatively depending on the level reached, and finally stipulated that growth would be maximized when it reaches a level of fifty-five percentage points in relation to the Gross Domestic Product, and would experience negative growth rates when this ratio reaches a level of one hundred and nine percentage points